Correlation Between Climate Indicators and COVID-19 Pandemic in Nigeria, Ghana, and South Africa - Bakare-Aremu, Tunde Abubakar; Ibrahim , Kekere Sule; Baba-Umar, Saadatu; Mamman, Rakiya (Jurnal Ilmu Ekonomi Terapan, 2023)
This study examines the relationship between climatic indicators (maximum temperature, minimum temperature, precipitation, and relative humidity) and the spread of COVID-19 using weekly data of confirmed cases and death rates from 3/25/2020 to 12/30/2020 for Nigeria, South Africa, and Ghana. Using an ex-post research design and descriptive method of analysis, the results of the study confirm evidence of correlation between climatic variables and the spread of the COVID-19 virus among the three selected countries. However, the policy recommendation that emanates from this study is that climate mitigation policies can be promoted as pandemic prevention policies, thus making a stronger case for their implementation to forestall future reoccurrence.